A new species of Leptobasis from Costa Rica (Odonata: Coenagrionidae) - Paulson, Dennis R. (Zootaxa, 2009)
Leptobasis guanacaste is described from seasonal wetlands in dry forest in Guanacaste, Costa Rica. It is unique among the five species of the genus in thoracic color pattern and the structure of the male terminal appendages and female mesostigmal laminae and appears to be closest to L. candelaria through similarities in genital ligula, male metafemur, and female ovipositor.